The role of salivary gland elastosonography in Sjögren's syndrome: preliminary results. (15th September 2014) - Gunes Tatar, Idil; Altunoglu, Hale; Kurt, Aydin; Altunoglu, Alparslan; Ozturk, Mehmet Akif; Erten, Sukran; Hekimoglu, Baki
Abstract Aim There is a need for a reliable, noninvasive radiological method for the assessment of salivary gland changes in Sjögren's syndrome (SS). The aim of this study was to evaluate the role of elastosonography as a noninvasive, sonographic modality evaluating tissue stiffness for salivary gland involvement in SS. Method We examined the stiffness in parotid and submandibular glands of 23 patients diagnosed with SS and 20 healthy volunteers. Elasticity scores of the salivary glands were classified into four groups according to the degree of the elasticity of the glands. Results The elasticity scores of the parotid and submandibular glands did not show a statistically significant difference between the patients with SS and the healthy volunteers. On the other hand, there was a significant relationship between the duration of the symptoms and the elasticity score of the parotid glands and left submandibular glands (P < 0.05). Patients with higher duration of symptoms had higher elasticity scores. Conclusion The results might suggest that with the progression of the SS, the elasticity scores of the parotid glands increase gradually, indicating that ultrasonic elastosonography has the potential to demonstrate the progression of the disease. The utility of elastosonography in the follow‐up of SS needs to be evaluated with larger studies.